Land Use Maps Database System of Water Resources by Application a Smartphone to Smart Farmers’ 4.0 - Lowanichchai, Sudajai; Prachai, Sangpetch; Chamnanphon, Kosin; Rattanasuporn, Jessada; Krongsrima, Krit; Chinjoho, Parinya; jongmuanwai, benjapuk (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2021)
The research in objective aimed for; 1) studying support guidelines and factors to affect accessing the database system of land use maps from water resources by application smartphone, 2) developing database system of land use maps from water resources by application smartphone, 3) assessing a applied performance to database system of land use maps from water resources by application smartphone of agriculture farmers’. That have to the key informant and sampling zine there are farmers in the Huai Sub Pradu reservoir area, Nakhon Ratchasima Province 261 samples. The collection by documentary study, interview, and questionnaire to the data. The research found that to; 1) support guidelines to access in the database had to incorporating measures into data layer components that enable users to quickly find information, convenient and comprehensive, able to make decisions in planning and utilization as appropriate to the potential of land use from water resources, in which of factors to affect accessing the database system consists of the collection of land use data in a database with a geographical map, creating knowledge for farmers to receive information about the water situation, land use for agriculture decisions, the management of land use and water management for efficiency, and is a direct and indirect influence factors with statistical significance at the level of .01, 2) database system of land use maps from water resources by application smartphone in 4 important components were the application system of data recording for agricultural preparation, reporting systems for water user members, the system for reporting land location map data, and water source warning information system, 3) applied performance to database system of land use maps from water resources by application smartphone of agriculture farmers’ for making knowledgeable about application usage, representing 76 percent, and satisfaction level to database system at a level of high levels. Which the database system is beneficial to farmers makes it possible to plan water use of efficiency.